Camrelizumab plus gemcitabine and oxaliplatin (GEMOX) in patients with advanced biliary tract cancer: a single-arm, open-label, phase II trial - Jian Wang; Hao Wu; Jing Sun; Xiao Li; Yongqian Shu; Xiaofeng Wu; Guoqiang Wang; Huajun Li; Xiaofeng Chen; Yanhong Gu; Yang Shao; Qianwen Shao; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors monotherapy has been studied in patients with advanced biliary tract cancer (BTC). The aim of this study was to assess the efficacy and safety of camrelizumab, plus gemcitabine and oxaliplatin (GEMOX) as first-line treatment in advanced BTC and explored the potential biomarkers associated with response.Methods In this single-arm, open-label, phase II study, we enrolled stage IV BTC patients. Participants received camrelizumab (3 mg/kg) plus gemcitabine (800 mg/m2) and oxaliplatin (85 mg/m2). Primary endpoints were 6-month progression-free survival (PFS) rate and safety. Secondary endpoints were objective response rate (ORR), PFS and overall survival (OS). Exploratory endpoints included association between response and tumor mutational burden (TMB), blood TMB, dynamic change of ctDNA and immune microenvironment.Results 54 patients with advanced BTC were screened, of whom 38 eligible patients were enrolled. One patient withdrew informed consent before first dose treatment. Median follow-up was 11.8 months. The 6-month PFS rate was 50% (95% CI 33 to 65). Twenty (54%) out of 37 patients had an objective response. The median PFS was 6.1 months and median OS was 11.8 months. The most common treatment-related adverse events (TRAEs) were fatigue (27 (73%)) and fever (27 (73%)). The most frequent grade 3 or worse TRAEs were hypokalemia (7 (19%)) and fatigue (6 (16%)). The ORR was 80% in patients with programmed cell death ligand-1 (PD-L1) tumor proportion score (TPS) ≥1% versus 53.8% in PD-L1 TPS <1%. There was no association between response and TMB, blood TMB, immune proportion score or immune cells (p>0.05), except that PFS was associated with blood TMB. Patients with positive post-treatment ctDNA had shorter PFS (p=0.007; HR, 2.83; 95% CI 1.27 to 6.28).Conclusion Camrelizumab plus GEMOX showed a promising antitumor activity and acceptable safety profile as first-line treatment in advanced BTC patients. Potential biomarkers are needed to identify patients who might respond to camrelizumab plus GEMOX.Trial registration number NCT03486678.